Taguchi-Grey Optimisation of TIG Welding Parameters and Its Impact on the Mechanical Properties of Austenitic Steel - Afabor A. Martins,; Onyekpe B,; Awheme Oghenerobo, (Journal of Advanced Industrial Technology and Application, 2025)
Welding, albeit tungsten inert gas welding; is a unique and widely adopted joining process especially for austenitic stainless steel arising from its advantages over other welding process. However very often, mechanical properties and weld quality could be deteriorated if the weld parameters are not controlled during a welding operation. Selecting the appropriate process parameters for welding operations is crucial for forming weld microstructures with excellent mechanical properties, thereby enhancing weldment performance during service. Thus in this study, the integrated Taguchi-Grey optimisation technique has been adopted in the optimisation of welding parameters. The Taguchi L27 orthogonal array design of experiment consisting of three levels of four factors of current, voltage, speed and gas flowrate was deployed for the determination of multi performance index for the output parameters of tensile strength and microhardness. The results obtained, after a confirmatory test to validate the predictive model indicates that there was an improvement from 0.0409 to 0.495 in MRPI, for the optimal parameters setting of current at 95 A, speed at 0.7 mm/s, voltage at 25 V and gas flow rate at 20 L/min respectively. This study could influence industrial practices by improving weld quality, reducing material wastage, and enhancing process efficiency. For example, optimizing welding parameters can minimise defects in aerospace applications or lead to stronger, lighter components in automotive manufacturing, improving both safety and performance.  Potential cost savings could also be achieved from optimised parameter selection and reduced trial and-error approaches in industrial applications. This methodology can also be adapted to other materials or welding techniques like friction stir welding or laser welding.